Insights in Pt-based electrocatalysts on carbon supports for electro-oxidation of carbohydrates: an EIS-DEMS analysis - Castañeda-Morales, Eleazar; Gómez-Gómez, Fabio A.; Li, Yueyin; Manzo-Robledo, Arturo (Frontiers in Chemistry, 2024)
In this work, the electrochemical oxidation of carbohydrates (glucose, fructose, and sucrose) was induced at the interface of Pt-nanoparticles supported on different carbon-based materials as carbon vulcan (C) and carbon black (CB). It was found that the support plays an important role during carbohydrates electro-oxidation as demonstrated by electrochemical techniques. In this context, current-concentration profiles of the redox peaks show the behavior of the pathways at carbohydrates-based solutions. Herein, the trend of current measured was glucose > sucrose > fructose, attributed to differences in the organic functional groups and chain-structure. Raman, XRD, SEM-EDS and XPS put in clear important structural, morphological, and electronic differences linked with the intrinsic nature of the obtained material. Differential Electrochemical Mass Spectroscopy (DEMS) indicated that the selectivity and the conversion of the formed reaction products during oxidation is linked with the catalyst nature (distribution, particle size) and the interaction with the carbon-based support.